2017
DOI: 10.1021/acs.energyfuels.7b01467
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Effect on Gas Hydrate Formation in the Presence of Additives

Abstract: Additives such as surfactants, polymers, salts, and hydrophobic particles are well-known (and used) to influence gas hydrate formation (GHF). This paper reviews and discusses the mechanisms of their effects. The effects of additives on GHF appear to vary greatly from one additive to another. Even a given additive can change from a promoter to an inhibitor and vice versa when the working conditions are changed. The available literature cannot explain the diverse effects of additives. We argue that the hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 141 publications
4
104
0
Order By: Relevance
“…Thus, by analyzing the enthalpy of carbon dioxide hydrate dissociation in the absence and presence of different chemical additives, it is found that maximum energy is used to destruct the hydrogen bonds between the water molecules in the hydrate structure. A thermodynamic hydrate inhibitor prevents the formation of hydrates by destroying water activity through hydrogen bonding 38 . The inhibition mechanism of combined inhibitors reduces molecule activity, thus increase the competition for water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, by analyzing the enthalpy of carbon dioxide hydrate dissociation in the absence and presence of different chemical additives, it is found that maximum energy is used to destruct the hydrogen bonds between the water molecules in the hydrate structure. A thermodynamic hydrate inhibitor prevents the formation of hydrates by destroying water activity through hydrogen bonding 38 . The inhibition mechanism of combined inhibitors reduces molecule activity, thus increase the competition for water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Dry water, a free-flowing powder prepared by mixing water and hydrophobic silica nanoparticles, has been recently introduced as kinetics and thermodynamic promoter [2,7,8,14,15,[32][33][34][35][36][37]. Dry water as a special encapsulated product has been resembled to reverse micelle and microemulsion systems that are formed by hydrophobic nanoparticles surrounding an aqueous core suspended in a nonpolar medium such as air [33,38].…”
Section: Fatemeh Golkhou Ali Haghtalab*mentioning
confidence: 99%
“…Nguyen and Nguyen [89] explained that the hydrophobic part of QAS (organic cation) acts as a hydrate promoter, while the hydrophilic part (anion) acts as a hydrate inhibitor. It creates two competitive effects on gas hydrate formation, the effects of salt depend on which effect is dominant in the working condition.…”
Section: Salt Effectsmentioning
confidence: 99%